Does the Microbiome Cause B27-related Acute Anterior Uveitis?. (3rd July 2016) - Rosenbaum, James T.; Lin, Phoebe; Asquith, Mark
ABSTRACT: The microbiome is strongly implicated in a broad spectrum of immune-mediated diseases. Data support the concept that HLA molecules shape the microbiome. We provide hypotheses to reconcile how HLA-B27 might affect the microbiome and in turn predispose to acute anterior uveitis. These theories include bacterial translocation, antigenic mimicry, and dysbiosis leading to alterations in regulatory and effector T-cell subsets. Received 31 October 2015; revised 7 January 2016; accepted 8 January 2016; published online 22 March 2016